Pterostilbene Alleviates Cholestasis by Promoting SIRT1 Activity in Hepatocytes and Macrophages - Ma, Chuanrui; Xiang, Jiaqing; Huang, Guixiao; Zhao, Yaxi; Wang, Xinyu; Wu, Han; Jiang, Kewei; Liang, Zhen; Kang, Lin; Yang, Guangyan; Yang, Shu (Frontiers in Pharmacology, 2021)
Background and purpose: FXR is a promising target for the treatment of human cholestatic liver disease (CLD). SIRT1 is a deacetylase which promotes FXR activity through deacetylating FXR. Pterostilbene (PTE) is an activator of SIRT1. However, the role of PTE in cholestasis has so far not been investigated. We examined whether PTE treatment alleviate liver injury in DDC or ANIT-induced experimental cholestasis, and explored the underlying mechanisms. Experimental approach: Mice with DDC- or ANIT-induced cholestasis were treated with different dose of PTE. Primary hepatocytes and bone marrow derived macrophages were used in vitro to assess the molecular mechanism by which PTE may improve CLD. Identical doses of UDCA or PTE were administered to DDC- or ANIT-induced cholestasis mice. Key results: PTE intervention attenuated DDC or ANIT-induced cholestasis. PTE inhibited macrophage infiltration and activation in mouse liver through the SIRT1-p53 signaling pathway, and it improved hepatic bile metabolism through the SIRT1-FXR signaling pathway. Compare with UDCA, the same doses of PTE was more effective in improving cholestatic liver injury caused by DDC or ANIT. Conclusions and implications: SIRT1 activation in macrophages may be an effective CLD treatment avenue. Using CLD models, we thus identified PTE as a novel clinical candidate compound for the treatment of CLD.